If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 2(3x + 10) = -4 Reorder the terms: 2x + 2(10 + 3x) = -4 2x + (10 * 2 + 3x * 2) = -4 2x + (20 + 6x) = -4 Reorder the terms: 20 + 2x + 6x = -4 Combine like terms: 2x + 6x = 8x 20 + 8x = -4 Solving 20 + 8x = -4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + 8x = -4 + -20 Combine like terms: 20 + -20 = 0 0 + 8x = -4 + -20 8x = -4 + -20 Combine like terms: -4 + -20 = -24 8x = -24 Divide each side by '8'. x = -3 Simplifying x = -3
| Y+7=-89 | | 4x-y=1.5 | | 16-v-8v=-6v-7v | | 4x^2+9y^2-8x-140=0 | | X^4-4x^3+6x^2-4x=y^2 | | X^2+21-13=0 | | 3y=6-6x | | (48-6)3*2= | | 2x-8=7x-38 | | (5x+x)+0=5+1 | | -38-5k=-7k+8(6k+1) | | 6x-2(3+2x)+5=19 | | n/8=3/32 | | 6m-8=3+9m | | T=-16t^2+112t+6 | | 3n-5+12=5 | | 130=-16x^2+112t+6 | | 5x+2+3x=2(x+10) | | 0=-16x^2+112t+6 | | 15r-4=12r-8 | | H(t)=-16x^2+112t+6 | | 7-42=49 | | 2+2(-5v-4)= | | 5p+1=1+5p | | 2X^2-8X^4= | | 2x+4(x+6)=78 | | 0.04w=15 | | 3x+10(-x+11)=-6 | | 3t=30+6t | | (x+8)=2(4x+5) | | 8+y=12+-1y | | 58k+35=6 |